Principals’ Leadership Skills for Teachers’ Job Performance: A Conceptual Perspective - Ndu-Ogbuji Chisa Judith (International Journal on Integrated Education, 2022)
A school principal requires a series of appropriate leadership skills to bring the school, staff, and students to a high level of achievement and to maintain school effectiveness. The thrust of this paper centred theoretically on examining the leadership skills necessary to enhance teachers’ job performance. Several scholarly articles were reviewed to buttress the arguments of the researcher, though some concepts differed because of the perspective of scholars. The paper concluded that the importance of teachers in any educational institution of teaching-learning cannot be overemphasized. This is because of the central role they play as implementers of the curriculum at the classroom level. Hence, the leadership skills of the principal are vital as they are often the key factor of difference between effective and ineffective educational systems. This paper suggested, amongst others, that school principals should be pragmatic and dynamic in the application of leadership skills and styles based on the level of morale of their teachers. Also, principals should always supervise teachers in their classes, and their supervision should not aim at fault-finding or witch-hunting, but should aim at improving the quality of instruction and learning situations.